Effect of Coronary Anatomy and Myocardial Ischemia on Long-Term Survival in Patients with Stable Ischemic Heart Disease. Issue 2 (February 2019) - Weintraub, William S.; Hartigan, Pamela M.; Mancini, G.B. John; Teo, Koon K.; Maron, David J.; Spertus, John A.; Chaitman, Bernard R.; Shaw, Leslee J.; Berman, Daniel; Boden, William E.
Abstract : Background: The severity of coronary artery disease (CAD) and of ischemia are evaluated to guide therapy, but their relative prognostic importance remains uncertain. Accordingly, we sought to clarify their association with long-term survival in the COURAGE trial (Clinical Outcomes Utilizing Revascularization and Aggressive Drug Evaluation). Methods and Results: Survival data from after the original trial period ended was obtained at 15 Veterans Affairs sites and 13 of 18 United States non–Veterans Affairs sites. Date of death was obtained from the Veterans Affairs system-wide Corporate Data Warehouse and the National Death Index. Of the original 2287 patients in COURAGE, 1370 (60%) had both stress perfusion imaging and quantitative coronary angiography available, with extended survival evaluated in 767 subjects. Survival was calculated by the Kaplan–Meier method, and a Cox proportional-hazards model adjusted for baseline differences. There were 369 all-cause deaths during a median follow-up of 7.9 years (range, 0–15 years). The number of coronary arteries diseased predicted survival (HR, 1.25; 95% CI, 1.09–1.43), whereas severity of ischemia did not (HR, 0.99; 95% CI, 0.80–1.22). Percutaneous coronary intervention did not offer a survival advantage over optimal medical therapy (HR, 0.95; 95% CI, 0.77–1.16) and there was no interaction between therapeutic strategy and number of coronary arteries diseased or severity of ischemia. In fully adjusted models, the number of coronary arteries diseased was not associated with increased mortality. Conclusions: In univariate analysis, the number of coronary arteries diseased predicted long-term mortality, but severity of ischemia did not. Adjusted for baseline variables, neither assessment approach predicted mortality. Overall, there was no survival benefit from percutaneous coronary intervention in any subset defined by either angiographic or ischemic severity. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT00007657. Abstract : Supplemental Digital Content is available in the text.